Best Poster Overall - Irish health sciences librarians supporting national clinical guideline development (Journal of EAHIL, 2017)
This article describes how a new national group of health sciences librarians was established in Ireland to support the development of national clinical guidelines, the topic of a poster presented at EAHIL 2014.